1,528 new students are now part of UMP family - Mimi Rabita, Abdul Wahit (2021)
KUANTAN, 8 October 2021 - A total of 1,528 new students who registered to study at the bachelor’s degree level at Universiti Malaysia Pahang (UMP) for the 2021/2022 academic session are now a part of the large UMP family.